2019
DOI: 10.1101/544817
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modelling Subject Variability in the Spatial and Temporal Characteristics of Functional Modes

Abstract: Recent work has highlighted the scale and ubiquity of subject variability in observa ons from func onal MRI data (fMRI). Furthermore, it is highly likely that errors in the es ma on of either the spa al presenta on of, or the coupling between, func onal regions can confound cross-subject analyses, making accurate and unbiased representa ons of func onal data essen al for interpre ng any downstream analyses.Here, we extend the framework of probabilis c func onal modes (PFMs) [Harrison et al. ] to capture cros… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 183 publications
(249 reference statements)
0
7
0
Order By: Relevance
“…In our previous work, we showed that simulated data containing *only* interindividual variation in node spatial maps resulted in a substantial amount of interindividual information in temporal network matrices estimated with ICA-DR (Bijsterbosch et al, 2018). There, the spatial information in the simulated data (i.e., the simulation ‘ground truth’) were subject-specific PFM maps, which are known to contain spatial overlap (Harrison et al, 2019; Harrison et al, 2015). Therefore, the theory above provides a clean (and mathematical) explanation for how the ‘ground truth’ spatial correlations present between PFM spatial maps can contaminate temporal correlations estimated from traditional ICA-DR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work, we showed that simulated data containing *only* interindividual variation in node spatial maps resulted in a substantial amount of interindividual information in temporal network matrices estimated with ICA-DR (Bijsterbosch et al, 2018). There, the spatial information in the simulated data (i.e., the simulation ‘ground truth’) were subject-specific PFM maps, which are known to contain spatial overlap (Harrison et al, 2019; Harrison et al, 2015). Therefore, the theory above provides a clean (and mathematical) explanation for how the ‘ground truth’ spatial correlations present between PFM spatial maps can contaminate temporal correlations estimated from traditional ICA-DR.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative parcellation method, designed to avoid the spatial independence constraint, is PROFUMO. This adopts a hierarchical Bayesian framework that includes spatial priors (for map sparsity and group map regularisation) and temporal priors (consistent with the hemodynamic response function) (Harrison et al, 2019; Harrison et al, 2015). The Probabilistic Functional Mode (PFM) maps obtained from PROFUMO commonly show relatively extensive amounts of spatial overlap (and hence spatial correlation) between nodes.…”
Section: Introductionmentioning
confidence: 99%
“…This forms a complete probabilistic model for the data, and the group-and subject-level information is inferred together via a variational Bayesian inversion scheme. This is covered in more detail in Harrison et al (2019).…”
Section: Resting-state Networkmentioning
confidence: 99%
“…In the same cohort of 18 infants, nine resting-state networks were robustly identified from separate resting-state scans using probabilistic functional mode analysis 17,18 (Figure 2). These included three sensory and motor networks (two visual, two auditory, and two somatomotor networks) and three cognitive networks (default mode, dorsal attention, and executive control networks).…”
Section: Nine Resting-state Network Were Replicable Across the Nocicmentioning
confidence: 99%
“…The resting-state network analysis performed on the 18-infant nociception-paradigm dataset was closely matched to that described for the dHCP dataset 24 . In brief, probabilistic functional mode (PFM) analysis using FSL's PROFUMO 17,18 was run on both datasets with a pre-specified dimensionality of 25, and using the infant double-gamma HRF 23,41 as the temporal prior. PROFUMO's Bayesian model complexity penalties can eliminate modes, thus returning a number of group-level modes that can be less than the pre-specified dimensionality.…”
Section: Resting-state Network Amplitudesmentioning
confidence: 99%